Suleiman the Magnificent, Sang Penakluk Timur dan Barat: Kajian Politik Ekspansi Turki Utsmani, 1520-1566 Masehi - Hafiez, Muhammad Ryan; Suwirta, Andi; Iriyadi, Achmad (INSANCITA, 2017)
ABSTRAKSI: Sultan Suleiman I dikenal juga dalam dunia Islam dengan gelar âAl-Qanuniâ, yang artinya âpembuat undang-undangâ; sedangkan dalam dunia Eropa, ia dijuluki dengan gelar âSuleiman the Magnificentâ atau âSolomon the Greatâ, yang bermakna âhebatâ, karena luas kekuasaannya menyaingi Alexander the Great. Artikel ini mengkaji proses ekspansi yang dilakukan oleh kesultanan Turki Utsmani di bawah kepemimpinan Sultan Suleiman I. Metode penelitian sejarah yang digunakan meliputi heuristik, kritik sumber, interpretasi, dan historiografi. Suleiman I merupakan Sultan Turki Utsmani ke-10, yang berkuasa dari tahun 1520-1566 Masehi. Di bawah kepemimpinannya, Turki Utsmani telah melakukan ekspansi ke wilayah Barat (Eropa Timur), wilayah Selatan (Mediterania dan Afrika Utara), serta wilayah Timur (Asia Barat). Ekspansi tersebut dilatarbelakangi oleh faktor-faktor geopolitik, ekonomi, dan keagamaan, yang kemudian berkembang menjadi peperangan. Di wilayah Barat, Turki Utsmani harus menghadapi kerajaan Hongaria dan Habsburg dalam memperebutkan daerah Belgrade dan Buda. Di wilayah Selatan, Turki Utsmani harus menghadapi kerajaan Spanyol dalam memperebutkan daerah Tunisia, Aljir, dan Mesir. Sedangkan di wilayah Timur, Turki Utsmani harus menghadapi Persia-Safavid dalam memperebutkan daerah Baghdad. Penaklukan Sultan Suleiman I telah memperluas wilayah Turki Utsmani dari 576,900 mil persegi pada tahun 1520 menjadi 877,888 mil persegi pada tahun 1566.KATA KUNCI: Ekspansi; Geopolitik; Ekonomi; Suleiman the Magnificent; Turki Utsmani.Â ABSTRACT: âSuleiman the Magnificent, the Conqueror of East and West: Study on Political Expansion of Ottoman Empire, 1520-1566 ADâ. Sultan Suleiman I was known in the Islamic world with the title of âAl-Qanuniâ, which means âlegislatorsâ; whereas in the European world, he is known by the title of âSuleiman the Magnificentâ or âSolomon the Greatâ, because his vast power to rival Alexander the Great. This article examines the expansion process carried out by the Ottoman empire under the leadership of Sultan Suleiman I. The historical method used includes heuristics, criticism of sources, interpretation, and historiography. Suleiman I was the Sultan of the 10th Ottoman empire, which ruled from 1520 to 1566 AD (Anno Domini). Under his leadership, the Ottoman empire had expanded to West region (Eastern Europe), South region (Mediterranean and North Africa), and East region (West Asia). The expansion is motivated by geopolitics, economics, and religion factors, which later evolved into the war. In the West region, the Ottoman empire had to conpront with Habsburg and Hungarian kingdoms in the fight over Belgrade and Buda areas. In the South region, the Ottoman empire had to face the Spanish kingdom in the fight areas of Tunisia, Algiers, and Egypt. While in the East region, the Ottoman empire must face the Persia-Safavid kingdom in fighting the Baghdad area. The conquest of Sultan Suleiman I have expanded the territory of the Ottoman empire of 576,900 square miles in 1520 became 877,888 square miles in 1566.KEY WORD: Expansion; Geopolitics; Economics; Suleiman the Magnificent; Ottoman Empire.Â Â Â Â About the Authors: Muhammad Ryan Hafiez, S.Pd. adalah Alumni Departemen Pendidikan Sejarah FPIPS UPI (Fakultas Pendidikan Ilmu Pengetahuan Sosial, Universitas Pendidikan Indonesia), Jalan Dr. Setiabudhi No.229 Bandung, Jawa Barat, Indonesia. Andi Suwirta, M.Hum. dan Drs. R.H. (Raden Haji) Achmad Iriyadi adalah Dosen Senior di Departemen Pendidikan Sejarah FPIPS UPI di Bandung, Jawa Barat, Indonesia. Alamat emel penulis: suwirta.sahaja@upi.eduHow to cite this article? Hafiez, Muhammad Ryan, Andi Suwirta & Achmad Iriyadi. (2017). âSuleiman the Magnificent, Sang Penakluk Timur dan Barat: Kajian Politik Ekspansi Turki Utsmani, 1520-1566 Masehiâ in INSANCITA: Journal of Islamic Studies in Indonesia and Southeast Asia, Vol.2(1), February, pp.17-30. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 2443-1776. Chronicle of the article: Accepted (January 15, 2017); Revised (January 29, 2017); and Published (February 27, 2017).